MOF-derived hierarchical core-shell hollow iron-cobalt sulfides nanoarrays on Ni foam with enhanced electrochemical properties for high energy density asymmetric supercapacitors. (10th November 2019) - Le, Kai; Gao, Mengjiao; Liu, Wei; Liu, Jiurong; Wang, Zhou; Wang, Fenglong; Murugadoss, Vignesh; Wu, Shide; Ding, Tao; Guo, Zhanhu
Abstract: In this work, hierarchical core-shell hollow iron-cobalt sulfides nanoarrays supported on conductive nickel foam (Fe-Co-S/NF) were fabricated using metal-organic frameworks (MOFs) as the sacrificial templates. Delicately manipulating the etching/ion-exchange reaction between Co-MOF and FeSO4 and the subsequent solvothermal sulfurization led to the formation of hierarchical core-shell hollow nanostructure with FeCo2 S4 -nanosheets shell assembled on the Co3 S4 hollow nanoarrays. Owing to the complex composition and unique structure, the obtained Fe-Co-S/NF possessed abundant electroactive sites, short charge/ion diffusion path, rich redox reactions and good structural robustness, contributing to the boosted electrochemical performance as supercapacitor electrodes. Consequently, the obtained Fe-Co-S/NF electrode exhibited a specific capacitance of 2695 F g −1 at 1 A g −1, a favorable rate capability with 69.8% capacitance retention at 10 A g −1 (much higher than that of CoS/NF electrode, i.e., 36.3%), and a retention of 84% over 1000 cycles. Moreover, an asymmetric supercapacitor was assembled by engaging Fe-Co-S/NF and reduced graphene oxide (rGO) as cathode and anode, respectively. The obtained device delivered a high energy density of 43.6 W h kg −1 at a power density of 770 W kg −1, while maintaining a capacity retention of 89.6% after 5000 cycles. The robust electrochemical properties indicate that the Fe-Co-S/NF can be used as promising electrode materials for high performance supercapacitors applications. Graphical abstract: Image 1 Highlights: Unique core-shell hollow iron-cobalt sulfides nanoarrays/nickel foam were fabricated through a novel MOF templated method. The Fe-Co-S/NF had a high specific capacitance of 2695 F g −1 at a current density of 1 A g −1 . The assembled asymmetric supercapacitor achieved a high energy density of 43.6 W h kg −1 at a power density of 770 W kg −1 . The assembled asymmetric supercapacitor retained 89.6% of its capacitance over 5000 cycles.